Is waist to height ratio better at assessing cause-specific mortality risk than body mass index or waist circumference? A prospective analysis in a large U.S.-based cohort - Alpa V. Patel; Kierstin Faw; Erika Rees-Punia; Brad Heltemes; Clara Bodelon; Anita Peoples; Lauren E. McCullough; Lauren R. Teras (PLoS ONE, 2025)
Introduction Excess body fatness is an established risk factor for various types of chronic disease and all-cause mortality. Most previous studies are based on body mass index (BMI) as a general measure of adiposity, but whether measures of central adiposity that better represent metabolically active visceral fat, such as waist-to-height ratio (WtHR), may be better at predicting disease and mortality risks is less known. Materials and Methods Data from a large, prospective cohort in the U.S. including 50,618 women and 43,783 men (mean age of 67.3 years, predominantly non-Hispanic White), among whom 21,565 women and 26,758 men died during follow-up (1997–2018), were used to calculate multivariable-adjusted hazard rate ratios and 95% CIs for WtHR, BMI, and waist circumference in relation to total and cause-specific mortality. Results WtHR was strongly correlated with BMI (r = 0.81). After adjustment for BMI and other covariates, WtHR (≥0.55 vs. < 0.50) was positively associated with all-cause mortality risk in women (RR = 1.23, 95% CI 1.17–1.29) and men (RR = 1.11, 95% CI 1.06–1.17). BMI and WC were also independently, positively associated with subsequent mortality risk at a similar magnitude to WtHR. Associations persisted for all grouped causes of death in women and men, with the exception of cancer and Alzheimer’s disease mortality in men. Mortality associations with WtHR were generally stronger among individuals younger than age 70 years compared to older individuals. Discussion WtHR was associated with all-cause, cardiovascular disease, cancer, respiratory disease, and Alzheimer’s disease mortality in women and men at a magnitude similar to BMI or WC. Excess adiposity is an established major risk factor for premature death, but different measures may better predict mortality in different populations defined by age or other factors.